PENALAAN PARAMETER KENDALI GUPFC PADA SISTEM TENAGA MULTIMESIN MENGGUNAKAN ANT COLONY OPTIMIZATION (ACO) - , LUKITA WAHYU PERMADI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The establishment of power plan is needed to face the growth of electrical energy. The Delivery of electrical power to the load center is done through transmission with limited capacity. The operation of this system raises problems of power system stability. FACTS is possible to be applied in transmission line to improve power distribution in line and power system stability. GUPFC is a component of FACTS. Multimachine System with GUPFC has the power system stability, angular velocity changes, and electric power better than a system without GUPFC. This Study is to compare the stability between multimachine with GUPFC and without GUPFC. The controller used are PSS and POD. ACO technique is used to tune the controller parameter of PSS and POD. The research result shows that system with GUPFC-POD and PSS tuned by ACO could increase system stability. This proven by low value of the initial oscillations, overshoot, and settling time that happened, also new eigenvalue of sytem resides in left side of imaginary axis.